Food Sovereignty: An Emancipatory Human Right - Kashyap, Mrinal (My University, 2020)
The globalized neoliberal agricultural regime operates within a neocolonial context and was therefore built upon the ideologies, law, and legacy of the colonial-era. Both capitalism and colonialism, in theory, and in practice, share characteristics that are inherently contrary to the realization of human rights. Given that the human rights framework operates within a globalized capitalist economy, there are systemic barriers to the universal realization of human rights. This thesis holds that the concept of food sovereignty not only highlights this reality but presents a nuanced emancipatory path forward towards a post-capitalist world where universal human rights realization is not only possible but inherent to the functioning of food sovereignty itself. Food sovereignty presents as a praxis for Marxist agrarian theory in establishing an approach to closing the metabolic rift. The existence of the Food Sovereignty Movement also confirms the existence of the metabolic rift as the theoretical disconnect between capitalism and human rights which underpins the current agricultural system. As a concept, it accounts for the systemic obstacles to the universal realization of the right to adequate food while also providing an alternative food system centred on the decisions of small-scale food producers. Contrary to capitalist and colonialist approaches to food production, food sovereignty is concerned with universal access to culturally appropriate nutritious foods produced through ecological means. Through a combination of normative and descriptive claims, this thesis examines the official recognition and realization of the right to food sovereignty as a proxy of Marxist ideology. Food sovereignty empowers the rights-holder to ensure the continued realization of their right to adequate food in underscoring the fact that rights realization is not static in nature but, an ongoing endeavour. As such, the process called for to implement an alternative food system is one of decolonization.
Keywords: Food Sovereignty; human rights; colonialism; capitalism